PARTIAL FATTY ACID OXIDATION (P-FOX) INHIBITORS AND COMBINED THERAPY OF CARDIOVASCULAR COMPLICATIONS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - M. E. Statsenko; S. V. Turkina; S. N. Tolstov (Российский кардиологический журнал)
.